Perancangan Sistem Informasi Reservasi Dan Pembayaran Pada Shin Babyspa Berbasis Web - Hardiansah, Dika Reza; Amroni; Gusriyanti, Dwi Ayu (LPPM STIKOM Dinamika Bangsa, 2024)
Abstract− Shin Babyspa is a company that provides spa services for babies located at Jl. Sultan Thaha Wirotho Agung Village, Rimbo Bujang District, Tebo Regency, Jambi Province. However, Shin baby spa has problems with the reservation and payment systems because the system currently running at Shin baby spa is still not computerized. Besides that, not all parents have enough free time, especially if parents are also workers. In the data processing process where customers register manually by taking notes, such as recording in a large number of baby registration books so that they take up space to be stored in a filing cabinet and it takes time to search customer data to create the Shin baby spa administration section. The purpose of this study was to design a web-based baby spa service information system that is able to provide solutions to the problems faced by Shin baby spas. The stages that will be carried out in solving the problems discussed are identifying, conducting information searches based on theoretical foundations, analyzing and collecting data through observation and interview techniques in order to resolve Shin Babyspa's issues. The waterfall model is used for system development, and the PHP programming language and MySQL database management system are used to carry out this research. to create applications for data processing that are intended to make data processing and report creation easier. Keywords: Design, Sistem, Informatics, Sistem Informasi, Reservation and payment